ヒガシ ナンキョク タイリク ミズホ コウゲン ノ セキセツ ソウイ カイセキ ニオケル ショモンダイ ダイ1カイ ナンキョク キスイケン シンポジウム - 渡辺, 興亜; ワタナベ, オキツグ; 加藤, 喜久雄; カトウ, キクオ; 佐藤, 和秀; サトウ, カズヒデ; WATANABE, Okitsugu; KATO, Kikuo; SATOW, Kazuhide (国立極地研究所, 1979)
P(論文) みずほ150mコアの積雪層位解析に関連して検討された2,3の問題について報告する.まず,層位構造要素が積雪形成過程でのどのような現象と関連するかを検討し,その結果に基づいて,合理的な基本層位単元の取り扱いについて述べた.次に季節層および年間積雪層形成における欠層現象,およびそれと積雪形成の地域特性との関連について検討した.氷床各地のある期間における平均降水量の推定の不落かな理由は,この欠層現象の量的評価が困難なことにあることを示した.また,積雪層中の酸素同位体組成(δ^<18>0)について,多積雪域であるW46地点から得られた資料をもとに検討した.単位層内のその分布は,それが堆積後の積雪の変態過程で生じた後生的なものである可能性を示している.δ^<18>0プロファイルの解釈には,今後改めて検討すべき多くの課題が含まねている. Long-term variation of precipitation and surface temperature in the vicinity of Mizuho Station were studied by means of stratigraphic analyses of 150-m boring core. ln this paper, some problems on snow stratigraphy aroused concerning the analyses are discussed. First, problems on the unit of stratification are discussed in relation to visible stratigraphic elements and deposition-erosion processes Second, phenomena of missing layer corresponding to the hiatus in the layer formation are discussed in relation to regional characteristics of those occurrence and frequency. Precise estimation of mean annual accumulation in a certain perlod may be impossible without quantitative rating of hiatus duration, and establishment of an effective method of rating should be the most important subject for the stratigraphic study. δ^<18>O vertical profiles in snow layer are investigated using the data obtained from high-accumulation area (W46,1958 m a s.l,) in terms of reconsideration of the classical interpretation. As a result, it is found that a part of δ^<18>O oscillation was due to the variation by isotopic discrimination under snow metamorphism departmental bulletin paper